Does the oil palm (Elaeis guineensis) generate a negative impact on the soil? A review - Pérez Hernández, Hermes (2022)
Introduction. Oil palm (Elaeis guineensis) is one of the perennial monocultures that has spread to almost a little more than nineteen million hectares in the world. Its expansion has generated social, economic, and political debate in various tropical countries. One of the problems that has been discussed is the impact on the physicochemical, biological, and ecological properties of the soil. Objective. (i) To provide a current overview of the expansion of oil palm cultivation in an area of the Soconusco region, Chiapas, Mexico, (ii) to document the effects caused by oil palm on the physicochemical and biological properties of the soil, and (iii) to present some proposals for management practices to increase the fertility and abundance of soil macroinvertebrates. Development. The search for keywords was carried out in the “topics” section within the “Web of Science” database from the year 2009 to March 2018. Research that relates the cultivation of oil palm with physical parameters, soil chemicals, and biology was consulted. The literature demonstrates the negative effects generated by oil palm monoculture on some physicochemical properties of the soil and the ecology and biology of the edaphic macrofauna. Conclusion. Evidence is show that the poor management of oil palm monoculture has environmental implications. The integration of good sustainable management practices could mitigate damage to the soil.